Higher education students perceptions of NNESTs’ language proficiency: will it affect their learning effectiveness? - Bing, Xiaoyi; Gao, Xiaoqing; Yang, Zhen (Frontiers in Psychology, 2023)
Increasingly, higher education institutions are giving more attention to the language proficiency of non-native English-speaking teachers (NNESTs) due to their growing numbers. Despite a recent surge in the literature on NNESTs in the global discourse of English language teaching (ELT), the impacts of NNESTs' language competency within the higher education systems of their countries remain woefully under-examined. Of particular concern is the absence of students' voices. Therefore, this study explores higher education students' perception of NNESTs' language proficiency. We recruited five NNESTs and five student focus groups (N=50). After estimating the language proficiency of the five NNESTs, we analyzed the post-observation transcripts. Our results show that while students concur that NNESTs' language proficiency contributes to their learning performance in class, other factors (e.g., the teacher's effective teaching style and charming personality, relaxed class atmosphere, the difficulty level of the teaching materials, and the learners' proficiency level) also perceived to play key roles in boosting students' class learning effectiveness. The findings highlight the need to include students in the design of teaching approaches, course design, and curricula, as well as the reflection process about NNESTs' language proficiency.